Removal of the Herbicide Molinate by Drinking Water Treatment Processes (Biological Sciences - PJSIR, 2007)
. The removal of mol i nate efficiency as an organ ic contaminant was evaluated by appl yi ng drinki ng water treatment processes. Water treatment processes viz., chlori nation, ozonation and activated carbon treatment were applied separatel y to water system. The level of molinate i n water reduced to 33% when it was treated with sodi um hypochlorite. In water system, 47 and 73% of this herbicide was dissipated by treatments of ozone and ozone combi ned with hydrogen peroxide , respectively. Powdered activated carbon (PAC) exhibited a better performance for the removal of mol inate as compared to granular activated carbon (GAC) and activated carbon removed this herbicide effecti vely. The association of ozonation with sodi um hypochlorite and activated carbon treatments were considered to be the best-tested treatment for the removal of mol i nate from water. Therefore, if mol i nate enters water as an organ ic contaminant , it could be removed effectively by drinki ng water treatment processes .